Sistemática, filogenia e biogeografia do grupo Characidium lauroi Travassos, 1949 (Characiformes, Crenuchidae) - Melo, Marcelo Roberto Souto de (2001)
The "Characidium lauroi" group is composed by five species, that inhabit small mountains streams, such as the tributaries of the Iguaçu, Paranapanema, Tietê and Paraíba do Sul rivers, and coastal streams between Ilha Grande bay and Ribeira de Iguape. Four of these species were described by Haroldo Travassos between the 1940's and 1960's, Characidium lauroi, C. japuhybense, C. schubarti e C. oiticicai, and two of them are new to the science, Characidium sp. "piabanha" e Characidium sp. “iguaçu”. Three sinapomorphies corroborate the monophily of the group: absence of parietal branch in the head laterossensorial system; small number of cromatophores in the transversal bars; and small rounded spots along the side of the body. The phylogenetic relationships among these species suggest that the history of isolating events among of the headwaters of southeastern Brazil was important for the species diversification process. Characidium japuhybense, which occurs only in coastal rivers, is the most basal species. Characidium lauroi and Characidium sp. "piabanha" form a monophyletic clade that is endemic to upper and middle Paraíba do Sul river drainages. The sister group of this clade is comprised of species that occur in the Parana drainage. The relationships among C. schubarti, C. oiticicai and Characidium. sp. “iguaçu” clade are poorly resolved, thus suggesting a putative recent and complex separation between the headwaters of the rivers Iguaçu, Tietê, Paranapanema and Ribeira de Iguape.